Isolation, Oxygen Sensitivity, and Virulence of NADH Oxidase Mutants of the Anaerobic Spirochete Brachyspira (Serpulina) hyodysenteriae, Etiologic Agent of Swine Dysentery - Stanton, Thad B. (American Society for Microbiology, 1999)
Brachyspira (Serpulina) hyodysenteriae, the etiologic agent of swine dysentery, uses the enzyme NADH oxidase to consume oxygen. To investigate possible roles for NADH oxidase in the growth and virulence of this anaerobic spirochete, mutant strains deficient in oxidase activity were isolated and characterized. The cloned NADH oxidase gene (nox; GenBank accession no. U19610) on plasmid pER218 was inactivated by replacing 321 bp of coding sequence with either a gene for chloramphenicol resistance (cat) or a gene for kanamycin resistance (kan). The resulting plasmids, respectively, pCmΔNOX and pKmΔNOX, were used to transform wild-type B. hyodysenteriae B204 cells and generate the antibiotic-resistant strains Nox-Cm and Nox-Km. PCR and Southern hybridization analyses indicated that the chromosomal wild-type nox genes in these strains had been replaced, through allelic exchange, by the inactivated nox gene containing cat or kan. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western immunoblot analysis revealed that both nox mutant cell lysates were missing the 48-kDa Nox protein. Soluble NADH oxidase activity levels in cell lysates of Nox-Cm and Nox-Km were reduced 92 to 96% compared to the activity level in parent strain B204. In an aerotolerance test, cells of both nox mutants were at least 100-fold more sensitive to oxygen exposure than were cells of the wild-type parent strain B204. In swine experimental infections, both nox mutants were less virulent than strain B204 in that fewer animals were colonized by the mutant cells and infected animals displayed mild, transient signs of disease, with no deaths. These results provide evidence that NADH oxidase serves to protect B. hyodysenteriae cells against oxygen toxicity and that the enzyme, in that role, contributes to the pathogenic ability of the spirochete.